Study of Environmental Carrying Capacity on the Development of Formal Housing in Moncongloe District, Maros Regency - Samsuddin Amin; Nurmaida Amri; Abdul Rachman Rasyid; Muhammad Faathir Nugraditama; Syifa Beby Alisha (EPI International Journal of Engineering, 2021)
Moncongloe District is an area with a relatively high population growth rate and distribution of housing, especially formal housing. This condition has implications for the tendency of increasing problems related to the carrying capacity of the environment and the suitability of land functions in the area. Therefore, it is necessary to harmonize the development of formal housing with the carrying capacity of the environment so that the negative impact of the phenomenon of formal housing development in this area can be avoided. The purpose of this study is to analyze the environmental carrying capacity of the development of formal housing for the prediction of the next 20 years. The analytical method used is a combined method of qualitative and quantitative analysis with a focus on the study of population projections, land availability and needs, and the carrying capacity of residential land. The results showed that the population in Moncongloe District in 2021 was 23,738 people, while the projected population in 2041 was 46,779 people, which means an increase of 97.06%. The results of the analysis of land availability show that 50% of the area of Moncongloe District is recommended for the development of residential land, including formal housing. The value of the carrying capacity of residential land (DDPm) in Moncongloe District in 2021 is 20.7 while in 2041 it is 20 so it can be concluded that the environmental carrying capacity in Moncongloe District can still accommodate the development of settlements for the next 20 years.